Growth of Accreting Supermassive Black Hole Seeds and Neutrino Radiation. (24th March 2015) - Ter-Kazarian, Gagik
Abstract : In the framework of microscopic theory of black hole (MTBH), which explores the most important processes of rearrangement of vacuum state and spontaneous breaking of gravitation gauge symmetry at huge energies, we have undertaken a large series of numerical simulations with the goal to trace an evolution of the mass assembly history of 377 plausible accreting supermassive black hole seeds in active galactic nuclei (AGNs) to the present time and examine the observable signatures today. Given the redshifts, masses, and luminosities of these black holes at present time collected from the literature, we compute the initial redshifts and masses of the corresponding seed black holes. For the present massesM B H / M ⊙ ≃ 1.1 × 1 0 6 to1.3 × 1 0 10 of 377 black holes, the computed intermediate seed masses are ranging fromM B H S e e d / M ⊙ ≃ 26.4 to2.9 × 1 0 5 . We also compute the fluxes of ultrahigh energy (UHE) neutrinos produced via simple or modified URCA processes in superdense protomatter nuclei. The AGNs are favored as promising pure UHE neutrino sources, because the computed neutrino fluxes are highly beamed along the plane of accretion disk, peaked at high energies, and collimated in smaller opening angle (θ ≪ 1 ).